The Moderating Effect of Subjective Well-Being and Proactive Personality in the Relationship between Job Insecurity and Turnover Intention Among Auditors - Fairiz Ayesha Achmad; Andi Ina Yustina (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2022)
This study examines whether job insecurity among auditors who work at a public accounting firm in Jakarta associates with their turnover intention and whether subjective well-being and proactive personality have a moderating effect. The data of the study were collected from a web-based questionnaire that amounted to 166 auditors in Jakarta, Indonesia, and used the SEM-PLS approach in testing the hypotheses. This study found that job insecurity has a positive relationship with turnover intention as well as a proactive personality relationship with turnover intention. This study found a negative relationship between subjective well-being and turnover intention. However, the moderating effect of subjective well-being and proactive personality was not proven in this study. Therefore, future studies are recommended to explore external turnover and test the construct in different fields or areas to get more significant results.